Thorny roses: the motivations and economic consequences of holding equity stakes in financial institutions for China's listed nonfinancial firms - Liping Xu; Yu Xin (China Journal of Accounting Research, 2017)
The reforms of China's financial system have significantly changed the country's financial sector. One noteworthy phenomenon is that many nonfinancial firms have obtained equity stakes in financial institutions. This study investigates the motivations behind and economic consequences of this recent proliferation of investments in financial institutions by nonfinancial listed firms. We find that the motivations for holding equity stakes in financial institutions include alleviating the pressure of industry competition, reducing transaction costs, and diversification to reduce risk. These investments, however, have double-edged effects on the performance of the investing firms. While their investment income increases, their operating income and overall return on assets decrease, as the investment income cannot compensate for the decrease in other operating income. The investing firms' cost of debt also increases, their cash-holding decreases, and stock price performance does not improve after investing in financial institutions. These effects contrast with the enthusiasm nonfinancial listed firms have for investing in financial institutions. The empirical findings in this study can inform financial industry regulators and decision-makers in listed firms. We advise nonfinancial firms to be cautious when considering investing in financial institutions.
Keywords: 650; Mixing of banking and commerce; Holding equity stakes in financial institutions; Motivations; Economic consequences